"No Overly Suggestive Photos of Any Kind": Content Management and the Policing of Self in Gay Digital Communities. (24th February 2015) - Roth, Yoel
<x xml:space="preserve">Abstract</x> This article examines the policies and practices that manage user‐submitted content on 3 gay‐targeted social networking services. While managing user‐generated content is a common practice across social networking services, the policies implemented on gay‐targeted services tend to be distinctively restrictive in scope and highly specific in formulation. This analysis identifies the technical, legal, and social affordances that authorized the creation of these policies. Framing content management policies as derived from the technical rules of platforms such as Apple's App Store obscures normative judgments about proper self‐presentation and community formation. Identifying the normative character of these policies requires an analysis rooted simultaneously in technology studies, media policy, and subcultural identity politics.